A place for joy in a joyful place: An exploration of city development in Lindholmen, Gothenburg, focusing on a recreational building as a more value-making destination, using an architectural fairytale as method for design - Herou, Tuva (My University, 2024)
What is joy, what is imagination? And how could a place be designed to stimulate these feelings as well as filling a function relevant for the area nearby? This master thesis is based on a wish of creating a physical space that may bring more wellbeing to citizens of Gothenburg, by function and story as well as physical expression. The word wellbeing may contain several aspects, some might link it to laughter, some might link it to health. In this thesis the word wellbeing seeks to arise from the roots of fantasy inspiring architecture and from the presence of sustainable development by plants and cultivation. Incorporating imaginativeness in the design, an architectural fairytale has been made, which the design relates to in process and appearance. The wish of the fairytale is not only to create an interesting base for design and for the creative process, but also to awaken a discussion about how different appearances of architecture may contribute to different moods. To anchor the design in a relevant context, a site with potential has been chosen, a preliminary site plan has been made, and in this area the design investigations take place. The program of the design is designing a building with the purpose of functioning as a recreational, cultivation-related park building, in collaboration with schools and businesses nearby, at the same time offering more value to its surroundings by its physical expression and working as a destination object for the whole city. The building is to be placed in a correlated park, whose appearance is investigated in relation to the site and its future plans of development. In the explorations phase, five different examples of the building are made, based on the fairytale and correlated moods. The explorations are further on the base for the final design, which consist of the building Plantheon and the surrounding park The Filurin park. Aspects of importance working with the thesis have been creative sketching, sustainability through cultivation, exploring fantasy awakening expressions through design, social inclusion through involving social organizations, and gain of general knowledge by contact with stakeholders and study visits of relevance.
Keywords: Recreational building, fantasy inspiring design, sustainability through cultivation, city park, architectural fairytale, joy in architecture, incorporation of business and surroundings, cultivation with schools, city development, creative sketching